A qualitative analysis of the needs and wishes of people with type 2 diabetes and healthcare professionals for optimal diabetes care. Issue 9 (23rd June 2022) - Vasconcelos Silva, Carina; Bird, Dominique; Clemensen, Jane; Janda, Monika; de Camargo Catapan, Soraia; Fatehi, Farhad; Gray, Len; Menon, Anish; Russell, Anthony
Abstract: Aim: Globally, type 2 diabetes care is often fragmented and still organised in a provider‐centred way, resulting in suboptimal care for many individuals. As healthcare systems seek to implement digital care innovations, it is timely to reassess stakeholders' priorities to guide the redesign of diabetes care. This study aimed to identify the needs and wishes of people with type 2 diabetes, and specialist and primary care teams regarding optimal diabetes care to explore how to better support people with diabetes in a metropolitan healthcare service in Australia. Methods: Our project was guided by a Participatory Design approach and this paper reports part of the first step, identification of needs. We conducted four focus groups and 16 interviews (November 2019 – January 2020) with 17 adults with type 2 diabetes and seven specialist clinicians from a diabetes outpatient clinic in Brisbane, Australia, and seven primary care professionals from different clinics in Brisbane. Data were analysed using reflexive thematic analysis, building on the Capability, Opportunity, Motivation and Behaviour model. Results: People with diabetes expressed the wish to be equipped, supported and recognised for their efforts in a holistic way, receive personalised care at the right time and improved access to connected services. Healthcare professionals agreed and expressed their own burden regarding their challenging work. Overall, both groups desired holistic, personalised, supportive, proactive and coordinated care pathways. Conclusions: We conclude that there is an alignment of the perceived needs and wishes for improved diabetes care among key stakeholders, however, important gaps remain in the healthcare system.